1996
DOI: 10.1071/pp9960285
|View full text |Cite
|
Sign up to set email alerts
|

Defective Infection and Nodulation of Clovers by Exopolysaccharide Mutants of Rhizobium leguminosarum bv. trifolii

Abstract: The biological and symbiotic properties of two types of exopolysaccharide deficient (Exo- phenotype) mutants of Rhizobium leguminosarum were investigated. One mutant, a pss1 derivative (ANU437) of R. l. bv. trifolii, produces very low levels of acidic exopolysaccharide (EPS) and of the acidic oligosaccharide (AOS) repeating unit lacking its O-acetyl substituent. The second strain, originally a R. I. bv. viciae derivative, but containing a clover pSym plasmid (Exo-1 mutant ANU54(pBRIAN)), did not produce any EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…However, the EPS charge in the first (physicochemical) step of adhesion seems to have minor contribution, whereas the hydrophobic properties of this polysaccharide play a more dominant role in this process. In several papers, the role of EPS in early stages of symbiosis (infection of host plant roots) is well documented (Rolfe et al 1996;Cheng and Walker 1998;Abreu et al 2012;Janczarek and Rachwał 2013). Other authors confirmed that rhizobial EPS was required for attachment to inert substrates, and additional bacterial components (adhesins, glucomannan, cellulose fibrils) are engaged in the further steps of this process (Laus et al 2006;Williams et al 2008).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the EPS charge in the first (physicochemical) step of adhesion seems to have minor contribution, whereas the hydrophobic properties of this polysaccharide play a more dominant role in this process. In several papers, the role of EPS in early stages of symbiosis (infection of host plant roots) is well documented (Rolfe et al 1996;Cheng and Walker 1998;Abreu et al 2012;Janczarek and Rachwał 2013). Other authors confirmed that rhizobial EPS was required for attachment to inert substrates, and additional bacterial components (adhesins, glucomannan, cellulose fibrils) are engaged in the further steps of this process (Laus et al 2006;Williams et al 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Besides flavonoids and Nod factors, rhizobial acidic exopolysaccharides (EPS) play a significant role in the establishment of an effective symbiosis especially with legumes that form indeterminate-type nodules (e.g. clover, pea, vetch, and alfalfa) (Rolfe et al 1996;Becker and Pühler 1998;Janczarek and Urbanik-Sypniewska 2013). This polysaccharide is indispensable for protection against host plant defence reactions and initiation and elongation of infection threads, special tubular structures via which rhizobia colonize root nodules (Cheng and Walker 1998;Jaszek et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Functions include homologs of the OmpA protein (COG2197), which is required for adhesion to both mammalian and fish epithelial cells in a range of Proteobacteria (23,24), Listeria internalin-like proteins, which enhance attachment and biofilm formation (25,26), and the widespread colonization island, which is essential for biofilm formation, colonization, and pathogenesis in a range of bacteria (27). Proteins related to the production and excretion of galactoglycan, or exopolysaccharide II, were more abundant in the U. australis community, and apart from forming part of the biofilm matrix, is also essential for the establishment and maintenance of symbiosis in several Rhizobium strains (28)(29)(30)(31)(32). GGDEF and EAL domain proteins, which are involved in the production and degradation, respectively, of bis-(3′-5′)-cyclic dimeric GMP (cyclic-di-GMP), were also detected at a higher abundance (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…Studies using GFP-marked S. meliloti revealed that succinoglycan is required early in the invasion process, as mutants unable to synthesize succinoglycan are enclosed in CCRH, but do not enable infection thread formation. Acidic exopolysaccharides now are known to be required for a number of other rhizobia to establish a symbiosis (4)(5)(6).…”
mentioning
confidence: 99%